SOLUTION-FOCUSED COUNSELING IN SOCIAL WORK (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The counseling in social work practice requires modern approaches for effective client assistance. The author compares the main principles of solution-focused counseling in social work with other approaches.Solution-focused approach is described as a postmodern, constructivist with a unique focus on resolving client's concerns. The basic assumption of the approach is that that people have positive untapped resources at the unconscious level that can be accessed by shifting their perspectives. Oriented toward the future, rather the past, the solution-focused approach states that clients have the right to determine their desired outcomes. It is affirmed that change occurs in a relatively short period of time, especially when clients are empowered and motivated to use their expertise to construct solutions.This approach has shown its efficacy in working with families and individuals in the psychotherapeutic context, but its principles are more universal and can also be used in the context of social work. The analysis of the effectiveness of solution-focused counseling, the role settings of the client, tactical and strategic elements of counseling support within the framework of this model were conducted in this article. The strategy of solution-focused, experience, possibilities and prospects of its application in counseling social work are analyzed.The article provides a review of studies which demonstrate the effectiveness of the solution-focused approach in the counselling process in social work.
Keywords: counseling strategies, solution-focusing, client choice, language of change.